Identification of ICF categories relevant for nursing in the situation of acute and early post-acute rehabilitation - Strobl Ralf; Grill Eva; Boldt Christine; Mueller Martin; Stucki Gerold (BMC, 2008)
Abstract Background The recovery of patients after an acute episode of illness or injury depends both on adequate medical treatment and on the early identification of needs for rehabilitation care. The process of early beginning rehabilitation requires efficient communication both between health professionals and the patient in order to effectively address all rehabilitation goals. The currently used nursing taxonomies, however, are not intended for interdisciplinary use and thus may not contribute to efficient rehabilitation management and an optimal patient outcome. The ICF might be the missing link in this communication process. The objective of this study was to identify the categories of the International Classification of Functioning, Disability and Health (ICF) categories relevant for nursing care in the situation of acute and early post-acute rehabilitation. Methods First, in a consensus process, "Leistungserfassung in der Pflege" (LEP) nursing interventions relevant for the situation of acute and early post-acute rehabilitation were selected. Second, in an integrated two-step linking process, two nursing experts derived goals of LEP nursing interventions from their practical knowledge and selected corresponding ICF categories most relevant for patients in acute and post-acute rehabilitation (ICF Core Sets). Results Eighty-seven percent of ICF Core Set categories could be linked to goals of at least one nursing intervention variable of LEP. The ICF categories most frequently linked with LEP nursing interventions were respiration functions, experience of self and time functions and focusing attention. Thirteen percent of ICF Core Set categories could not be linked with LEP nursing interventions. The LEP nursing interventions which were linked with the highest number of different ICF-categories of all were "therapeutic intervention", "patient-nurse communication/information giving" and "mobilising". Conclusion The ICF Core Sets for the acute hospital and early post-acute rehabilitation facilities are highly relevant for rehabilitation nursing. Linking nursing interventions with ICF Core Set categories is a feasible way to analyse nursing. Using the ICF Core Sets to describe goals of nursing interventions both facilitates inter-professional communication and respects patient's needs. The ICF may thus be a useful framework to set nursing intervention goals.